2011
DOI: 10.1103/physrevlett.106.181301
|View full text |Cite
|
Sign up to set email alerts
|

Large Non-Gaussianity in Axion Inflation

Abstract: The inflationary paradigm has enjoyed phenomenological success, however, a compelling particle physics realization is still lacking. The key obstruction is that the requirement of a suitably flat scalar potential is sensitive to Ultra-Violet (UV) physics. Axions are among the best-motivated inflaton candidates, since the flatness of their potential is naturally protected by a shift symmetry. We re-consider the cosmological perturbations in axion inflation, consistently accounting for the coupling to gauge fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
546
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(562 citation statements)
references
References 26 publications
15
546
1
Order By: Relevance
“…63 Besides the model-independent gravitational wave signal, a host of additional modeldependent signatures have been explored, including oscillations in the power spectrum [36], deviations from scale-invariance [759], non-Gaussianity [37,760], chiral gravitational waves [260,759], and primordial black holes [761]. Since all of these effects are tied to the underlying axion shift symmetry, one has the hope of finding correlated signatures across different observational channels.…”
Section: Phenomenologymentioning
confidence: 99%
“…63 Besides the model-independent gravitational wave signal, a host of additional modeldependent signatures have been explored, including oscillations in the power spectrum [36], deviations from scale-invariance [759], non-Gaussianity [37,760], chiral gravitational waves [260,759], and primordial black holes [761]. Since all of these effects are tied to the underlying axion shift symmetry, one has the hope of finding correlated signatures across different observational channels.…”
Section: Phenomenologymentioning
confidence: 99%
“…Instead of pursuing this computationally heavy task, we estimate the tensor perturbation by using the results based on analytic photon mode functions found in refs. [40][41][42], where the present energy density per logarithmic k interval of the gravitational waves relative to the critical density is given by…”
Section: Jhep02(2017)008mentioning
confidence: 99%
“…This may solve the long standing problem in the slow-roll inflation that a flat potential is required. Moreover, the curvature perturbation induced by the particle production has distinctive non-Gaussianities [40,41,47]. In the case of a quadratic inflation, the measurements of CMB power spectra and bispectrum has constrained the inflaton-photon coupling α < 32 [40,41,47].…”
Section: Jhep02(2017)008mentioning
confidence: 99%
See 1 more Smart Citation
“…In Refs. [32,33], it has been indicated that a coupling of the pseudoscalar inflaton field to the electromagnetic fields can generate non-Gaussianity [34,35] of power spectrum of the curvature perturbations coming from the quantum fluctuations of the inflaton field.…”
Section: Introductionmentioning
confidence: 99%